An update on B. G. Prasad’s socioeconomic scale: May 2016 - Vasudevan, Jyothi; Mishra, Amit Kumar; Singh, Zile (International Journal of Research in Medical Sciences, 2016)
Modified BG Prasad socioeconomic scale is a simple and widely used scale used by researchers to determine the socioeconomic status of study subjects in health studies in India. It is a scale based on the per capita income of an individual and hence has to be constantly updated to take inflation and depreciation of rupee into account. The consumer price index (CPI) for industrial workers (IW) is used to calculate updated income categories. The Consumer Price Index is updated every month and the same is available at the Labour Bureau of India website on the last day of every month. State-specific CPI values are also available on the Department of Labour website and should be used to determine more accurate income categories for the study area.